Consumer Bankruptcy and Financial Health - Dobbie, Will; Goldsmith-Pinkham, Paul; Yang, Crystal S. (The Review of Economics and Statistics, 2017)
This paper estimates the effect of Chapter 13 bankruptcy protection on financial health using a new data set linking bankruptcy filings to credit bureau records. Our empirical strategy uses the leniency of randomly assigned judges as an instrument for Chapter 13 protection. We find that Chapter 13 protection decreases an index measuring adverse financial events such as civil judgments and repossessions by 0.323 standard deviations and increases the probability of being a homeowner by 13.2 percentage points. Chapter 13 protection has little impact on open unsecured debt but decreases the amount of debt in collections by $1,333.